Poultry Production Messaging in Two National-Circulation Newspapers - Leslie D. Edgar; Donald M. Johnson; Stuart Estes (Journal of Applied Communications, 2017)
Consumers are concerned about the use of antibiotics and hormones in poultry. News media is the primary way consumers gain knowledge about this subject. This study assessed articles in an effort to describe and compare coverage of antibiotic and hormone use in poultry production from The New York Times (NYT) and The Wall Street Journal (WSJ) between 1994 and 2014. Content analysis methodology was used to assess selected articles (N = 265) to identify key messages about antibiotic and hormone use in poultry production, article type, type by year, and complete a comparison of focus, frames, and emergent themes. Five emergent themes were identified: 1) consumers awareness of and concern for antibiotic/hormone use in poultry production (NYT 38.8%, WSJ 51.2%); 2) the role of antibiotic use in poultry production in increased levels of antibiotic-resistant bacteria (NYT 43.8%, WSJ 24.4%); 3) regulation of antibiotic use in poultry production (NYT 35.0%, WSJ 31.7%); 4) purpose of antibiotic/hormone use in poultry production (NYT 32.5%, WSJ 29.3%); and 5) transparency of antibiotic use poultry production practices (NYT 15.0%, WSJ 12.2%). Articles were primarily news stories, and there was an increase in articles focused on antibiotic and hormone use in poultry over the 20-year period. NYT was 8.8 times more likely to write an editorial on one of these topics than was the WSJ. Recommendations include increased understanding and addressing consumer concern about antibiotic and hormone use in poultry production, increased transparency, and improved relations with media contacts who cover poultry production issues.
Keywords: Agricultural Communications; Content Analysis; National Newspapers; Poultry Production Messaging; Qualitative Research